2010
DOI: 10.1016/j.physd.2009.07.003
|View full text |Cite
|
Sign up to set email alerts
|

A nonequilibrium temperature and fluctuation theorem for soft-mode turbulence

Abstract: Non-thermal Brownian motion of a particle in soft-mode turbulence (SMT) in the electroconvection of a nematic liquid crystal has been experimentally investigated to clarify the statistical and thermodynamical aspects of SMT using the Lagrangian picture in hydrodynamics. The effective temperature for SMT is obtained in two different ways based on the definition of the diffusion coefficients due to non-thermal particle fluctuations: the Einstein relation and the fluctuation theorem. The temperatures from both me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…We experimentally found the dual structure of the modal autocorrelation in SMT and have theoretically revealed the mechanisms of the dual structure [29]. It has been reported that the spatiotemporal disorder in SMT generates non-thermal fluctuations [12,30] by which a nonMarkovian (i.e., memory) effect is expected to play a significant role in the relaxation dynamics.…”
Section: Introductionmentioning
confidence: 76%
“…We experimentally found the dual structure of the modal autocorrelation in SMT and have theoretically revealed the mechanisms of the dual structure [29]. It has been reported that the spatiotemporal disorder in SMT generates non-thermal fluctuations [12,30] by which a nonMarkovian (i.e., memory) effect is expected to play a significant role in the relaxation dynamics.…”
Section: Introductionmentioning
confidence: 76%
“…In preceding articles, we discussed how to describe the motion of a particle in SMT using a generalized version of the Langevin equation [4,6]. Thermal Brownian motion is accurately described by the Langevin equation,…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The random motion driven by nonthermal fluctuations or chaotic flows [1][2][3][4][5][6] has been investigated in the context of nonlinear physics and statistical mechanics far from equilibrium. Among these phenomena, motion dynamics driven by soft-mode turbulence (SMT) in the electroconvection of a nematic liquid crystal is interesting because of the existence of hierarchical structures such as locally aligned convective rolls and a globally disordered structure [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore natural to approach the turbulence problem from the perspective of nonequilibrium statistical mechanics [12,13,14,15,16]. The statistical properties of turbulence in connection with the deviation from equilibrium has been investigated from the angles of fluctuation-dissipation theorem (FDT) [17,18,19], fluctuation theorem [20,21,22,23], large deviation theory [24,25,26], and time asymmetry in Lagrangian statistics [27,28,29,30,31] among others.…”
Section: Introductionmentioning
confidence: 99%